The impact of organizational justice on job satisfaction in organizations: A case study on the employees of the faculty of law, university of bablon (Entrepreneurship Journal for Finance and Business, 2022)
The aim of this scientific research is to determine the relationship within the organizational justice variable and its impact on the performance of the workforce in organizations. In particular knowing how this research came to studying each dimension of justice and its impact on each other on the one hand, and on the other hand the role of dimensions. Organizational justice in increasing the degree of employee performance and gaining a competitive advantage in the labor market.The research sample was based on descriptive and explanatory statistics, where the researcher relied on collecting and statistic information and data from the research sample. Then, the research sample was handed over from all employees, a research questionnaire previously planned for this purpose. Where the data was analyzed and the results were known through the statistical programs for that.The research sample reached (195) from various workforces in the College of Law / University of Babylon, and data and responses were collected based on the random distilled sample method, and the size of the research sample was (57) employees working in the college.After reaching the results of the research sample, the results were discussed by presenting them to previous research on the same topic. Where the results of the targets were determined on the independent variable and its direct impact on the dependent variable in the research. Where the researcher conducted all the statistical methods, tests, correlation and regression coefficients, measures of central tendency. Finally, confirmatory factor analysis was performed for all variables and hypotheses.Where it was found through statistical methods and tests that there is a strong relationship with a high degree between each of the independent variables of the study sample with the dependent variable and the degree of influence of each of them on the research sample. Also, the role of organizational justice and its impact on increasing the degree of job satisfaction in the work environment was determined.